Original paperInfluence of zonal dosimetry on prostate brachytherapy outcomes - Hong, Cheng William; Reddy, Chandana A.; Wilkinson, Allan; Klein, Eric A.; Ciezki, Jay P. (Journal of Contemporary Brachytherapy, 2015)
Purpose: To examine the influence of zone-specific dosimetry on outcomes during permanent prostate implantation (PI), where the peripheral zone (PZ) and transitional zone (TZ) may receive varying radiation doses. Material and methods : Four hundred and sixteen patients treated with I-125 PI (target dose: 144 Gy) between 1996 and 2003 were included in this Institutional Review Board (IRB) approved, retrospective analysis. Whole prostate (WP), TZ, and PZ were contoured, and zone-specific D 90 and V 100 were computed. Their influence on biochemical failure (BF) was evaluated using Cox proportional hazards analysis. Results: The median age and initial prostate-specific antigen (PSA) was 68 years and 6.1 ng/ml, respectively, and the median follow-up time was 8.8 years. There were 329 subjects with Gleason score (GS) 6 disease (79.1%), and 82 subjects had GS 7 disease (19.7%). Androgen deprivation therapy (ADT) was used in 20.4% of patients. Median D 90 and V 100 % in the WP, PZ, and TZ were 141.2 Gy, 156.1 Gy, and 134.5 Gy; and 88.8%, 93.3%, and 84.2%, respectively. Ten-year rates for biochemical recurrence-free survival, distant metastasis-free survival, and prostate cancer-specific mortality were 82.4%, 92.4%, and 0.97% respectively. Only initial PSA, GS7+ disease, ADT, and PSA frequency were significant on multivariate analysis. Ten-year rates of grade 3 or higher GU and GI toxicity was 10.9% and 1.8%, respectively. TZ V 200 and TZ V 300 were significantly associated with late genitourinary toxicity. Conclusions : The TZ received significantly lower doses of radiation compared to the PZ. On multivariate analysis, no dosimetric parameter was associated with efficacy. Higher TZ doses may be associated with higher late GU toxicity without improving efficacy.